Pengaruh Motivasi dan Kompetensi Guru Terhadap Kinerja Guru Sekolah dan Madrasah di Lingkungan Pondok Pesantren Salafiyah Syafi’iyah Sukorejo - Hafid, Moh. (Jurnal Pendidikan Islam Indonesia, 2017)
This research was carried out at schools in Salafiyah Syafi’iyah Boarding School Situbondo with the population of 648 teachers, while the sample of 87 teachers used in this study. This research is a quantitative research, using multiple regression approach by SPSS 16 for windows. The results of this study are (1) Effect of teacher motivation (X1) on teacher performance (Y) obtained Fcalculate 4.906 and sig. (p) 0.029. That p value less than significance value a = 0,05 on the degree of freedom (df) = N – 2 = 87 – 2 = 85, table value on p value 95% (5% significance) is 1,697; (2) Effect of teacher competency (X2) on teacher performance (Y) obtained Fcalculate 1,118 and sig. (p) 0.000. Based on the probability value of X1 : p = 0,000 because of p < 0.05 so that Ho is rejected. It means that teacher motivation is affect on teacher performance. Based on the probability value of X2 : p = 0,032 because of p <0.05 so that Ho is rejected. This also means that teacher competency is affect on teacher performance.